OCEANIC VERSES OF THE QUR’AN AND THEIR POINTERS TO TECHNOLOGICAL SOLUTIONS - Mifedwil Jandra; Anhar Anshori; H. M. Kholili; Arif Rahman (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
This study aims to explore the phenomenon of the ocean recited in the verses of the Quran such as, fire/energy in the ocean, two oceans that do  not  blend,  deep  darkness  of  the  ocean,  sea  boundary,  oceanic layers,  and  the  abundant  wealth  of  the  sea  for  humanity.  This  article focuses first on the semantic aspects on oceanic verses as revealed and found  in  42  verses  in  the  Quran  and  then  how  these  verses  could  be used  as  guidance  for  technological  solutions.  The  study  uses  the method  of  interpretation  of  bir  rakyi  or  interpretation  within  reason using  the  scientific  method.  Modern  semantic  scientific  methods, ontology,  and  the  categorization  of  verses  are  used  for  further understanding  and  developing  a  framework  for  further  study  in developing  a  foundation  for  Islamic  Marine  Knowledge.  The  study findings indicate that the knowledge of layers in the seawater column, as  mentioned  in  the  Quran,  could  be  a  blessing  for  Muslims  to  be inspired and guided to find more discoveries and benefits of this water layer  phenomenon.  These  ancient  manuscripts  are  relevant  to  the challenges  of  modern  civilization,  such  as  food  and  energy  security and  environmental  control.  There  are  clues  in  these  oceanic  verses about  technological  solutions  to  the  existing  and  future  humanitarian problems, which Muslims can use as a divine guidance.